2021
DOI: 10.3390/ijerph18020461
|View full text |Cite
|
Sign up to set email alerts
|

Using Information and Communication Technologies (ICT) for Mental Health Prevention and Treatment

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
1
8
0
1
Order By: Relevance
“…This is also supported by previous studies examining age differences in the IMIs [51,54]. Besides age, other variables, such as e-health literacy, might affect the positive outcomes from IMIs; accordingly, such aspects should also be considered in the future [40,55]. Future studies should address older patients specifically in order to meet their needs better.…”
Section: Discussionsupporting
confidence: 71%
“…This is also supported by previous studies examining age differences in the IMIs [51,54]. Besides age, other variables, such as e-health literacy, might affect the positive outcomes from IMIs; accordingly, such aspects should also be considered in the future [40,55]. Future studies should address older patients specifically in order to meet their needs better.…”
Section: Discussionsupporting
confidence: 71%
“…Future research may want to prioritize these transdiagnostic variables in the corresponding modules of T-CBT programs. In addition, adolescents suffering from high levels of COVID-19-related anxiety and depression could benefit from transdiagnostic protocols delivered via internet (T-iCBT) (Sandín et al, 2020b;Fonseca and Osma, 2021). It has been suggested that internetbased interventions have several advantages compared with traditional face-to-face treatments, such as improved access to evidence-based treatments, a better cost-effectiveness and less stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Given the harmful effects many have recommended spreading awareness about various mental health disorders and explored using tele-medical and e-Health interventions for treatment of such cases as described by Fonseca et al [6].…”
Section: Related Workmentioning
confidence: 99%
“…This behaviour is also adopted to filter profanity and abusive language. For this, the profane-words package 6 is used which contains a large collection of profanity in English. The extension also packages a background script that warns the user if any of the blacklisted keywords are detected on a web site other than google search that the user visits with a popup as shown in Figure 2[B].…”
Section: Design and Developmentmentioning
confidence: 99%